Preparo e caracterização de nanopartículas lipídicas sólidas como sistema carreador conjunto para os herbicidas atrazina e simazina visando futuras aplicações em agricultura - Oliveira, Jhones Luiz de [UNESP] (2015)
Atrazine and simazine are triazine herbicides widely used in sugarcane and corn crops. Due to environmental and human health problems caused by excessive use of these herbicides, it is important to develop new formulations as less aggressive alternative. The aim of this study was to develop a system of modified release, based on solid lipid nanoparticles for encapsulation of both herbicides atrazine and simazine . In the first stage of the work the solid lipid nanoparticles (SLN) based in tripalmitin containing the herbicides atrazine and simazine were prepared by the method of diffusion evaporation of the solvent. The SLN were characterized for their physico-chemical properties (diameter, polydispersion, zeta potential and pH), encapsulation efficiency, particle interaction of herbicides and its components, concentration, morphology and release kinetic profile. The SLN were effective for encapsulation the herbicide, showing encapsulation efficiency of 90% to atrazine and 98% for simazine. The SLN showed hydrodynamic diameter between 255 nm and 300 nm, polydispersity index below 0.2 and the zeta potential about -17 mV. In function of time (120 days), all formulations remained stable, the SLN containing only simazine showed better physicochemical stability. The release kinetics assays showed that solid lipid nanoparticles modified the release profile of herbicides, delaying the release. The apparent flow data, showed that the organization of the herbicides within the particles occurs differently for together and separate encapsulation. The application of Korsmeyer-Peppas's mathematical model, showed that the release process is governed by anomalous transport. In the second part, evaluated the cytotoxicity and biological activity of these formulations. For tests with non-target organism Zea mays (maize), all formulations showed no phytotoxic effects when compared to control. In tests with target organism Raphanus raphanistrum (turnip), in...